Certolizumab pegol in severe hidradenitis suppurativa in pregnancy: A case report - Paolo Gisondi; Elena Montalto; Tea Curic; Elisabetta Danese; Francesco Bellinato; Giampiero Girolomoni (SAGE Open Medical Case Reports)
Hidradenitis suppurativa is a chronic inflammatory disease of the skin with a suppurative-cicatricial outcome affecting the infundibular component of the pilo-sebaceous unit. The lesions are typically localized in the intertriginous and apocrine gland-rich areas. Hidradenitis suppurativa mainly affects patients at a young age and is very often refractory to conventional medical treatment. During pregnancy, the management of hidradenitis suppurativa becomes demanding due to the need of safety therapies. Certolizumab pegol is a pegylated monoclonal TNF-α inhibitor that lacks the fragment crystallizable region preventing active placental transfer and could be used in pregnancy and lactation if clinically needed and is label for chronic plaque psoriasis, rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, Crohn’s disease. Herein, we describe a case of a 32-year-old pregnant woman with Hurley stage III hidradenitis suppurativa successfully treated with certolizumab pegol.